Associations between sleep disturbances and suicidal ideation, plans, and attempts in adolescents: a systematic review and meta-analysis. Issue 6 (7th March 2019) - Liu, Jen-Wei; Tu, Yu-Kang; Lai, Ying-Fan; Lee, Hsin-Chien; Tsai, Pei-Shan; Chen, Ting-Jhen; Huang, Hui-Chuan; Chen, Yu-Ting; Chiu, Hsiao-Yean
Abstract: Study Objectives: To systematically review and meta-analyze the associations between sleep disturbances and suicidal ideation, plans, and attempts in adolescents and explore potential moderators of these associations. Methods: Embase, PubMed, ProQuest, and the China Knowledge Resource Integrated Database were searched from their inception dates to October 19, 2018. We selected cross-sectional, prospective, or retrospective studies without time or language restrictions. Results: Nine cross-sectional studies, four prospective studies, and one retrospective report that, respectively, involved 37 536, 9295, and 80 adolescents were included in the meta-analysis. Cross-sectional analyses revealed that adolescents with sleep disturbances were at higher risks of suicidal ideation, plans, and attempts (pooled odds ratios [ORs] = 2.35, 1.58, and 1.92) than those without sleep disturbances. Prospective reports indicated that sleep disturbances in adolescents significantly predicted the risk of suicidal ideation but not suicide attempts (pooled ORs = 1.79 and 1.98, 95% confidence intervals = 1.36–2.36 and 0.62–6.29, respectively). The retrospective study did not support the association between sleep disturbances and suicide attempts. Depression did not moderate the associations between sleep disturbances and suicidal ideation or attempts in adolescents. Adolescents with insomnia complaints had a higher risk of suicidal ideation than those with other sleep complaints. Age, the female percentage, and reliable sleep measures were significant moderators (all p < .05). Conclusions: Sleep disturbances, particularly insomnia, should be considered an influencing factor when developing preventive strategies against adolescent suicidal ideation. Additional prospective studies are warranted to establish causality of sleep disturbances in youth suicide plans and attempts.